THE EDUCATIONAL E-BOOK-BASED VERBAL BULLYING ASSESSMENT SCALE (BVA) AS A TOOL FOR DETECTING BULLYING BEHAVIOR USING THE RASCH MODEL - Fiki Dwi Shofiyanto; Agustina Puspitarini; Aulia Karuniawati; Maria Wona Kerong; Ulfa Waqia; Khairul Bariyyah; Nining Maizura; Alief Laili Budiyono (CV. TOTUS TUUS, 2025)
Verbal bullying among junior high school students remains a critical issue due to its profound psychological, social, and academic consequences. The increasing prevalence of such behavior, coupled with the absence of reliable assessment tools, hinders early detection and intervention in school settings. This study aimed to develop and validate the Bullying Verbal Assessment (BVA) instrument in the form of an e-book, intended to identify instances of verbal bullying among students at SMPN 28 Malang. Using a quantitative approach, data were collected from 92 students selected through quota sampling. The instrument consisted of 41 items assessed using the Rasch Model through the Winsteps application. Results indicated that 16 items met the validity criteria (fit MNSQ values between 0.5–1.5, ZSTD within –2.0 to +2.0, and Pt Measure Corr values between 0.4–0.85), and the instrument achieved a reliability index of 0.69, falling into the moderate category. The findings confirm that the BVA instrument is valid and reliable for detecting verbal bullying behavior. The study provides a practical and accessible assessment tool for school counselors, enhancing early intervention strategies in addressing verbal bullying cases. Its digital format facilitates integration into school counseling programs, supporting both curative and preventive actions. For future research, expanding the demographic scope and exploring the instrument’s applicability across various education levels and digital platforms is recommended to strengthen its utility and impact in broader educational contexts.